Pluralism of Inheritance Law: Gender Justice in Islamic and Acehnese Customary Perspectives - Januddin Januddin; Muhammad Jafar; Nurlinda Yani (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the inheritance law system in Indonesia is expected to realize inclusive justice for all parties, including in terms of gender. However, in reality, the pluralism of law consisting of Islamic law, customary law, and civil law reveals fundamental differences in inheritance distribution, which often lead to inequality, particularly for women. This study aims to analyze how gender justice is understood and implemented within a plural inheritance law system, as well as how local practices in Aceh reflect the interaction between Islamic law and customary law. This article is categorized as a library research with a qualitative approach. The methodology used is normative legal study and comparative study. The results conclude that the pluralism of inheritance law in Indonesia provides flexibility in legal application but also has the potential to create legal uncertainty and gender injustice. From an Islamic perspective, inheritance distribution is based on distributive justice, while customary law shows variations depending on kinship systems. Local practices in Aceh demonstrate an integration of Islamic law and customary law through deliberation, although they do not yet fully reflect contextual gender justice.